Mortalidad por cáncer: experiencia previa y referencia futura, provincia de Tungurahua. 2000 –2014: Cancer mortality: previous experience and future reference, province of Tungurahua. 2000 –2014 (La U Investiga, 2019)
A cross - sectional non-experimental and trendswas carried out to describe the cancer mortality pattern in Tungurahua province during 2000 and 2014. The universe consisted of cancer deaths registered in both periods, registered in the National Institute of Statistics and Census of Ecuador. The gross mortality rate predominated in the canton Mocha during 2000 with 120.77 per 100000 inhabitants and in canton Cevallos with 165.87 in 2014, in females with 59.18% and 54.96%, and in digestive organs with 39.40% and 40.00% respectively. Most years of potential life lost (YPLL) contributed malignant neoplasms of stomach, male sex, the group of 55 to 59 years with 17.85 and 20.79 per thousand inhabitants, and female sex of 55 to 59 years in 2000 with 44.49, the group from 60 to 64 years old with 40.86 for 2015. The standardized mortality ratio increased by 1.2 in 2014. It is recommended that research be conducted into cancer mortality indicators.
Keywords: Mortality; Cancer; Potential Years of Potential Life